COMPOSITION AND STRUCTURE OF THE INTERFACIAL INTERFACE Si/Al(111) AND Si/Cu(111) - Ёркулов Руслан Махаммади угли (American Journals Publishing, 2024)
In this paper the results of experimental studies of the regularity of the formation of the interfacial boundary during the deposition of Si and Ge on the surface of single crystals Al(111) and Cu(111) are presented. Optimal modes of sputtering and annealing for obtaining semiconductor-metal systems have been established. The effect of barium ion implantation on the composition, morphology, electronic and crystal structure of the Si(Ge)/Cu(Al) system has been determined. The optimal temperature for the creation of nanoheterostructure has been shown Si-CuSi-Cu. Based on the data of the IPS and CPE, it was established for the first time that during the deposition of Si on the surface of Al and subsequent annealing, a bond between the Si and Al atoms is not formed.
Keywords: Heterostructure, nanofilms, nanophases, single crystal, energy loss by electrons, intensity, plasma oscillations, photoelectrons.